Analysis of the Translation Method of the Novel "The Gulliver's Travels" - Wijaya, Robin (Critical Review of English-Arabic World Journal, 2024)
This research is a qualitative research with descriptive-comparative quality. The purpose of the research is to identify the communicative translation method with transposition and modulation procedure by translating the novel “Gulliver’s Travels” from source to target text. This scientific work is dedicated as a research of translating a narrative text with casual language register. This aims to suit the readability level of target readers to shun discomfort in reading. In fact, communicative method intends to help target readers understand the translated text even though the content is not as similar as the source text. It prioritizes the accurate meaning delivery instead of using literal translation method. This method may assist the translator in creating an accurate translation to fix the sentence structures in source text that cannot be directly translated into target text. In addition, annotations are presented after finishing the translation of source text. This may present some additional information regarding cultures and particular words and phrases that were quite peculiar for the translator. Providing annotations can help the translator prevent from inaccurate word choice.